Syntheses, structural characterization and thermoanalysis of transition-metal compounds derived from 3,5-dinitropyridone - Fan, R.; Zhou, Q.P.; Zhang, G.F.; Cai, M.Y.; Li, P.; Gan, L.H.; Zhao, F.Q.; Li, J.Z.; Fan, X.Z.; Ng, S.W. (Kluwer (now part of Springer), 2010)
Nine metal compounds of Mn(II), Zn(II) and Cd(II) derived from dinitropyridone ligands (3,5-dinitropyrid-2-one, 2HDNP; 3,5-dinitropyrid-4-one, 4HDNP and 3,5-dinitropyrid-4-one-N-hydroxide, 4HDNPO) were characterized by elemental analysis, FT-IR and partly by TG-DSC. Three of which were further structurally characterized by X-ray single-crystal diffraction analysis. The structures of the three compounds, Mn(4DNP)(2)(H(2)O)(4), 4, Zn(4DNPO)(2)(H(2)O)(4), 8, and Cd(4DNPO)(2)(H(2)O)(4), 9, crystallize in the monoclinic space group P2(1)/n and Z = 2, with a = 8.9281(9), b = 9.1053(9), c = 10.6881(11) angstrom, beta = 97.9840(10)degrees for 4; a = 8.4154(7), b = 9.9806(8), c = 10.5695(8) angstrom, beta = 97.3500(10)degrees for 8; a = 8.5072(7), b = 10.2254(8), c = 10.5075(8) angstrom, beta = 96.6500(10)degrees for 9. All three complexes are octahedral consisting of four equatorial water molecules, and two nitrogen or oxygen donor ligands (DNP or DNPO). The abundant hydrogenbonding and pi-pi stacking interactions seem to contribute to stabilization of the crystal structures of the compounds. The TG-DTG results revealed that the complexes showed a weight loss sequence corresponding to all coordinated water molecules, nitro groups, the breaking of the pyridine rings and finally the formation of metal oxides.